2002
DOI: 10.1080/713738745
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Orientational Order Parameter in Various Liquid-Crystalline Phases

Abstract: Many methods for the determination of the order parameter in nematic liquid crystals are known. However, most of them are not applicable to cholesteric and smectic phases. Therefore, experimental data on the order parameter in cholesteric and smectic phases are hardly available. To determine the orientational order parameter S we exploited the de Gennes observation, that any anisotropic physical quantity may be a measure of orientational ordering in nematic mesophase. The order parameter can be calculated dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(47 citation statements)
references
References 13 publications
3
36
0
Order By: Relevance
“…4, the microscopic order parameter (S) as calculated from refractive indices data using the Vuks approach (relation) matches very well with macroscopic order parameter (Q) for nematic mixture E-24. Kuczyński [33] has suggested that one can expect that within a given local field they may be found to be nearly the same as is seen in the present study. The value of both order parameters decreases as temperature increases and shows a sharp change at nematic-isotropic transition temperature.…”
Section: Resultssupporting
confidence: 79%
“…4, the microscopic order parameter (S) as calculated from refractive indices data using the Vuks approach (relation) matches very well with macroscopic order parameter (Q) for nematic mixture E-24. Kuczyński [33] has suggested that one can expect that within a given local field they may be found to be nearly the same as is seen in the present study. The value of both order parameters decreases as temperature increases and shows a sharp change at nematic-isotropic transition temperature.…”
Section: Resultssupporting
confidence: 79%
“…Kuczynski et al [23] suggested an approximate empirical formula for normalization of the optical birefringence similar to that used by Haller [24] for polarizabilities. It has been shown that the nematic order parameter obtained from the optical anisotropy is equal to the one evaluated from magnetic polarizability anisotropy with the accuracy of ±5%.…”
Section: Theorymentioning
confidence: 99%
“…In this extrapolation one assumes that for temperatures far enough from the clearing point, the expression log χ (T ) [23] is a linear function of the logarithm of the reduced temperature. On the other hand, one postulates that the order parameter is equal to 1 at the absolute zero of temperature which means that all molecules are parallel to each other, i.e., lim T →0 [log( n)] = log n 0 .…”
Section: Theorymentioning
confidence: 99%
“…Journal of Molecular Liquids 174 (2012) [1][2][3][4] where Δn is the birefringence at perfect order (T = 0 K) and this can be obtained by following Kuczynski et al [3,4] and by using the following equation.…”
Section: Theorymentioning
confidence: 99%
“…Different physical properties of the liquid crystals (LCs) can be understood from the important parameter viz., the order parameter [1][2][3][4]. For the display technology, the knowledge of optical anisotropy, refractive indices and their temperature dependence is necessary [1].…”
Section: Introductionmentioning
confidence: 99%